PENGARUH PENYADAPAN DAN KADAR PEREKAT TERHADAP SIFAT PAPAN PARTIKEL TUSAM - Rozak Memed; I M Sulastiningsih; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The result of a study on the properties of particle board made from pine wood is reported in this paper. The pine as raw material was classified into three groups i.e. tapped, untapped, and combination of them. The particle board was manufactured by using urea formaldehyde resin with four levels i.e. 6%, 8%, 10%, and 12% by weight of wood dry basis.The result reveals that the average density of particle board made of tapped, untapped, and combination of them is 0.61 g/cm3, so that it can be classified as medium density particle board. The properties of particle board were affected by both tapping and glue proportion. However, density and internal bond were affected by glue proportion but not by the raw material.Except for water absorption, overall properties of particle board made from tapped pine appeared to have superior properties than that from untapped one.